To solve the system of equations, we can use the method of substitution or elimination.
Using the method of substitution:
From the second equation, we have x + y = 2. We can rearrange this equation to solve for x: x = 2 - y.
Substituting this value of x into the first equation, we get: 3(2 - y) + y = 3.
Expanding and simplifying, we have: 6 - 3y + y = 3.
Combining like terms, we get: -2y + 6 = 3.
Subtracting 6 from both sides, we have: -2y = -3.
Dividing both sides by -2, we get: y = 1.5.
Substituting this value of y back into the second equation, we have: x + 1.5 = 2.
Subtracting 1.5 from both sides, we get: x = 0.5.
Therefore, the solution to the system of equations is:
x = 0.5 and y = 1.5.
The correct answer is B. x = 0.5, y = 1.5.
12 of 1412 of 14 Items
07:45
Question
3x + y = 3
x + y = 2
Solve the system of equations.
Responses
A x = 12
, y = 3x = 1 2 , y = 3
B x = 3, y = 12
x = 3, y = 1 2
C x = 12
, y = 32
x = 1 2 , y = 3 2
D x = 32
, y = 12
x = 3 2 , y = 1 2
E x = 52
, y = -92
1 answer